Resource acquisition method and device, electronic equipment and computer readable medium - ZHANG HAN; SHENG XINZHE (2024)
The invention discloses a resource obtaining method and device, electronic equipment and a computer readable medium, and the method comprises the steps: when a page is being constructed, after a resource obtaining request is received, if the resource obtaining request is used for requesting to obtain resource data corresponding to a target component in the page, the target component in the page is obtained; if yes, theme resource information corresponding to the target component can be extracted from the cache space, so that the theme resource information can describe the theme state of the target component on the page; and determining resource data corresponding to the target component according to the subject resource information, so that the resource data can represent the actual state of the target component presented on the page, and the target component can be constructed on the page based on the resource data subsequently. In this way, the component construction process can be completed by using the su